Prosthodontic Care for Patients with Cleft Palate - Sowmya, S; Shadakshari, S; Ravi, MB; Ganesh, S; Gujjari, Anil Kumar (Journal of Orofacial Research, 2013)
Patients with cleft palate undergo various problems. The management of these patients by prosthesis has been a challenge for many years. Rehabilitation with prosthetictreatment helps patient psychologically to increases their selfesteem, and work to lead a normal life. A basic knowledge on managing these patients makes prosthodontist better equipped in handling emergencies if they arise. Hence, this review article addresses literature on the historical background, prevalence, etiology of the cleft palatal defect and the prosthodontic approaches available for rehabilitation.